System Balance and Fast Clocks - Smith, Burton (SC, 2005)
As clock rates have risen over the years, nearly all aspects of computer implementation from programming model (got caches? got cores?) to component technology have been forced to adapt. The falling cost of transistors has enabled some of this, but does not always help. For example, we have now reached clock rates even in CMOS where skin effect in copper-based transmission lines limits the global bandwidth of large-scale systems so strongly that optical interconnect looks like the only way to retain balance.